Kidney function at 3 months after acute kidney injury is an unreliable indicator of subsequent kidney dysfunction: the NARA-AKI Cohort Study. Issue 3 (11th May 2022) - Nishimoto, Masatoshi; Murashima, Miho; Kokubu, Maiko; Matsui, Masaru; Eriguchi, Masahiro; Samejima, Ken-Ichi; Akai, Yasuhiro; Tsuruya, Kazuhiko
ABSTRACT: Background: The relationship between kidney function at 3 months after acute kidney injury (AKI) and kidney function prognosis has not been characterized. Methods: This retrospective cohort study included adults who underwent noncardiac surgery under general anesthesia. Exclusion criteria included obstetric or urological surgery, missing data and preoperative dialysis. Linear mixed-effects models were used to compare estimated glomerular filtration rate (eGFR) slopes in patients with and without AKI. Multivariable Cox proportional hazard models were used to examine the associations of AKI with incident chronic kidney disease (CKD) and decline in eGFR ≥30%. Results: Among 5272 patients, 316 (6.0%) developed AKI. Among 1194 patients with follow-up creatinine values, eGFR was stable or increased in patients with and without AKI at 3 months postoperatively and declined thereafter. eGFR decline after 3 months postoperatively was faster among patients with AKI than among patients without AKI ( P = .09). Among 938 patients without CKD—both at baseline and at 3 months postoperatively—226 and 161 developed incident CKD and a decline in eGFR ≥30%, respectively. Despite adjustment for eGFR at 3 months, AKI was associated with incident CKD hazard ratio [HR] 1.73 [95% confidence interval (CI) 1.06–2.84] and a decline in eGFR ≥30% [HR 2.41 (95% CI 1.51–3.84)]. Conclusions: AKI was associated with worse kidney outcomes, regardless of eGFR at 3 months after surgery. Creatinine-based eGFR values at 3 months after AKI might be affected by acute illness-induced loss of muscle mass. Kidney function might be more accurately evaluated much later after surgery or using cystatin C values. Graphical Abstract: